Research on the Precise English Translation in the Export Trade of Chinese Special Agricultural Products (Journal of Global Humanities and Social Sciences, 2025)
In today’s era of expanding international trade markets and accelerating digital transformation, accurate translation of Chinese special agricultural products is crucial for their international market expansion. China has a multitude of unique agricultural products that hold significant positions in the international market. However, language and cultural differences lead to insufficient translation accuracy and a lack of unified standards, which severely restricts the enhancement of their international competitiveness. Based on the current problems faced by the translation of Chinese special agricultural products, this paper innovatively discusses the translation strategy of special agricultural products in the context of digital transformation and international trade, aiming to enhance the international influence of Chinese special agricultural products and promote the sustainable development of agriculture and cultural exchanges by constructing a scientific translation system and improving the translation quality.